Energy Development Initiatives of India and Thailand under BIMSTEC: Progress and Dynamics - Chaipala, Aksaraphak (WIMAYA, 2021)
The oil crisis in the early 1980s has triggered the necessity of finding oil reserves among non - oil producing countries. India and Thailand are both oil consumption countries. Because of the rapid economic development and high vehicular fuel consumption, India has become one of the top five oil consumption countries in the world. Thailand though has less population but the demand for oil energy is still increasing. From the geopolitics perspective, Myanmar is country with abundant oil resource that located between Thailand and India, become a vital geo – economics subject for both countries. Bilateral cooperation, between India - Myanmar and Thailand - Myanmar attests the importance of Myanmar in both regards. By visiting Myanmar, India’s ministry of energy has strengthened the energy cooperation between India and Myanmar. Meanwhile, Thailand, as a natural gas consumer from both the Yadana and Yetakun, in the Gulf of Mottama or Arakan, Myanmar, has hiked up her import of natural gas from Myanmar. The agreements in the 1990s have resulted in the increase of oil imports to India and Thailand. The oil demand for both countries could lead India and Thailand into competitors. Thanks to the policy of energy cooperation between India and Thailand, their attempts are to build multilateral partnership in order to increase the capability to strengthen energy connectivity from Myanmar. By making the connectivity more convenient and efficient has led to the creation of BIMSTEC Gas Pipeline project. Myanmar as the energy leader in BIMSTEC has placed Thailand, Myanmar, India and other countries in the framework of cooperation. In the future energy will play an important role to strengthen the cooperation in BIMSTEC which highly oil consumption still continuously. This article aims to show that the cooperation like BIMSTEC can guarantee the energy dependence for Thailand and India in the future. It will also analyze their related policy formulation, such as the plan for an alternative energy security.